Anton 2: raising the bar for performance and programmability in a special-purpose molecular dynamics supercomputer - Shaw, David E.; Grossman, J. P.; Bank, Joseph A.; Batson, Brannon; Butts, J. Adam; Chao, Jack C.; Deneroff, Martin M.; Dror, Ron O.; Even, Amos; Fenton, Christopher H.; Forte, Anthony; Gagliardo, Joseph; et al. (Proceedings of the International Conference for High Performance Computing, Networking, Storage and Analysis, 2014)
Anton 2 is a second-generation special-purpose supercomputer for molecular dynamics simulations that achieves significant gains in performance, programmability, and capacity compared to its predecessor, Anton 1. The architecture of Anton 2 is tailored for fine-grained event-driven operation, which improves performance by increasing the overlap of computation with communication, and also allows a wider range of algorithms to run efficiently, enabling many new software-based optimizations. A 512-node Anton 2 machine, currently in operation, is up to ten times faster than Anton 1 with the same number of nodes, greatly expanding the reach of all-atom biomolecular simulations. Anton 2 is the first platform to achieve simulation rates of multiple microseconds of physical time per day for systems with millions of atoms. Demonstrating strong scaling, the machine simulates a standard 23,558-atom benchmark system at a rate of 85 μs/day---180 times faster than any commodity hardware platform or general-purpose supercomputer.